Pengaruh Konsep Diri Dan Forgiveness Terhadap Psychological Well-Being Pada Mahasiswa - Afiifah oktafiani rahmadini nurul khootimah; Afrian riziq; Suniyah salasilla; Lucky purwantini (Journal of Student Research, 2024)
Psychological well-being indicates an individual's ability to make life decisions independently, master their environment, establish positive relationships with other people, determine and achieve life goals, accept themselves positively, and develop their potential gradually. This research aims to determine the influence of self-concept and forgiveness on psychological well-being. This research uses quantitative methods. The subjects in this research were 134 students of the psychology study program at the Islamic University "45" Bekasi. The sampling technique used is simple random sampling. The data analysis technique used is multiple linear regression. The results of this research show that the F test result is a calculated F value = 153.579 with a significance value of 0.000 < 0.05 and the R2 value shows that self-concept contributes 70.1% to psychological well-being. Self-concept has a significant influence on psychological well-being, while forgiveness does not have a significant influence.